Społeczne, ekonomiczne i własnościowe uwarunkowania funkcjonowania Biblioteki Kórnickiej w XIX i XX wieku - Osiewała, Renata (Acta Universitatis Lodziensis. Folia Historica, 2010)
For the first time the Kórnik estate came into possession of the Działyńskis family in 1676. Count Tytus Działyński, the son of Ksawery and Justyna Dzieduszycka, was the most famous of this family. In 1825 he took over the fortune of Kórnik, and one year later he founded one of the most valuable book collcction, known today as the Kórnik Library of the Polish Academy of Sciences. The ancestors of Tytus: grandfather Augustyn and father Ksawery, assembled the first collection. Among the books there were works in the field of Polish law (editions from 16th, 17th and 18th century), historical works of such authors as Jan Długosz, Joachim Bielski, Stanisław Orzechowski, Łukasz Górski, Stanisław Leszczyński, books on religious problems and hagiography. The books mostly concerned the history of Poland and Poles in their glorious times. Many of them discussed the period of partitions of Poland. From the beginning the intention of Tytus Działyński was to create a centre worthy of the Partia Library and to run a publishing house in the future. In 1861 his son, Jan Kanty Działyński inherited the collection. At that time in Kórnik there were 25 000 of works in 40 000 volumes, together with alnost 1000 valuable manuscripts. During the course of his life, Jan Kanty Działyński considerably enlarged the collection. He died childless on 30th March 1880. The heir to the property was his nephew, citizen of France, Władysław Zamoyski. The new owner of Kórnik, persecuted by the German invader was banned from effectively claming legal rights to his property. As a result, he entrusted Zygmunt Celichowski with running the estate. In 1924 Władysław Zamoyski formulated a project of the National Foundation “Zakłady Kórnickie”, which was approved in 1925 by the lower chamber of the Polish Parliament. Consequently, the collection became legally property of the Polish nation. In 1953 the collection was taken over by the Polish Academy of Sciences. From then on, the Kórnik Library has been enjoying its eminent scientific status and is one of the main the PAN’s libraries making its collection available exclusively for scientific purposes.